Chapter XII, Article III: Offenses Affecting Public Safety, undated, reprinted in Digest of the Acts Repealing the Charters of Certain Municipal Corporations?and the Ordinances of the Taxing District of Shelby County, Tennessee 188, 189 (C.W. Heiskell ed., 1882). - (:unkn) unknown (My University, 1882)
To carry concealed on or about the person any pistol, bowie-knife, dirk or other deadly weapon. Or to carry any pistol, slung-shot, dangerous knife, or any other deadly weapon of like character at all or in any manner, except in self-defense or while executing some law, or to carry through the streets or other public place in the District, any loaded gun. Also prohibited the discharge of firearms
Keywords: CARRY - CONCEALED; DISCHARGE